2017
DOI: 10.5194/acp-2017-198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of aerosol direct effects on tropospheric ozone through changes in atmospheric dynamics and photolysis rates

Abstract: <p><strong>Abstract.</strong> Aerosol direct effects (ADE), i.e., scattering and absorption of incoming solar radiation, reduce radiation reaching the ground and the resultant photolysis attenuation can decrease ozone (O<sub>3</sub>) formation in polluted areas. One the other hand, evidence also suggests that ADE associated cooling suppresses atmospheric ventilation thereby enhancing surface-level O<sub>3</sub>. A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 8 publications
1
33
0
Order By: Relevance
“…The cloud fraction in the lowest layer also increased over the ocean. As the lower PBLH over land prevented the ventilation of pollutants over the surface, air pollution became worse, especially near sources of emissions (Wang et al, ; Xing et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cloud fraction in the lowest layer also increased over the ocean. As the lower PBLH over land prevented the ventilation of pollutants over the surface, air pollution became worse, especially near sources of emissions (Wang et al, ; Xing et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…To achieve a more thorough understanding of meteorology, air quality, and their interaction, we must identify the effects of aerosols on the radiative budget (Wong et al, ). A number of studies have used satellite data and numerical models to quantify both the direct and indirect effects of aerosols and meteorological (climatological) responses (Haywood & Boucher, ; Jacob & Winner, ; Takemura et al, ; Wang et al, ; Wong et al, ; Xing et al, ; Xing et al, ; Xing et al, ; Yu et al, ). Xing et al () found that the direct effect of aerosols increases the concentration of surface air pollutants as a result of the stabilization of the atmosphere, which reduces ventilation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, aerosols decrease soil pH through N and sulfur (S) deposition, which may accelerate leaching and reduce the availability of nutrients to plants, leading to C loss (Bowman et al, ). Furthermore, sulfate aerosols can oxidize photosynthesis tissues (Eliseev, ), and other aerosols affect the photochemical processes producing near‐surface ozone (Xing et al, ), which impairs stomatal conductance and photosynthesis (Sitch et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major factors influencing the change in ozone concentration in a polluted hazy atmosphere, as mentioned in the earlier studies, is the reduction in solar radiation within the lower boundary layer due to aerosol forcing and feedbacks (Jiang et al, ; Li et al, ; Wong et al, ). Some studies also provide evidence of increase in surface level O 3 with aerosol feedback linked to suppressed atmospheric ventilation (Chen et al, ; Xing et al, ) rather than photochemistry. The observed increase in O 3 in the present study (at Kharagpur) may be associated with reduced ventilation (due to the decrease in boundary layer height and wind speed), which enhanced the precursor levels (CO and NO x in Figure ) and thus increased photochemistry resulting in greater O 3 chemical formation.…”
Section: Resultsmentioning
confidence: 99%